2004
DOI: 10.1111/j.1365-246x.2004.02279.x
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectric structure of the Dharwar Craton from magnetotelluric studies: Archean suture identified along the Chitradurga-Gadag schist belt

Abstract: S U M M A R YBroad-band magnetotelluric data were collected at 50 stations over a 400 km long, approximately east-west profile over the granite-greenstone terrain of Dharwar, southern India. The tensor decomposed data were interpreted using a 2-D inversion scheme. The geoelectric model is suggestive of a suture along the Chitradurga-Gadag schist belt, formed by the thrusting of the West Dharwar Craton beneath its eastern counterpart, with an easterly dip of 20-30 • . The thrust proposed here pre-dates the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Support for the inferred configuration of the upper crustal layer in the region near Makthal comes from magnetotelluric studies by Ramaprasada Rao et al (2003), who inferred a mid crustal layer between depths of 11-16 km. Similar findings have been reported earlier from magnetotelluric studies (Gokarn et al 2004) and gravity and magnetic studies (Ramadass et al 2007;Ramadass et al 2006;Himabindu and Ramadass, 2004) as well.…”
Section: Narayanpet-irladinne Areasupporting
confidence: 89%
“…Support for the inferred configuration of the upper crustal layer in the region near Makthal comes from magnetotelluric studies by Ramaprasada Rao et al (2003), who inferred a mid crustal layer between depths of 11-16 km. Similar findings have been reported earlier from magnetotelluric studies (Gokarn et al 2004) and gravity and magnetic studies (Ramadass et al 2007;Ramadass et al 2006;Himabindu and Ramadass, 2004) as well.…”
Section: Narayanpet-irladinne Areasupporting
confidence: 89%
“…Magneto-telluric (MT) studies carried out by Gokarn et al (2004) in the western Dharwar Craton indicates thinning of the lithosphere due to hot spot activity and it is associated with high conductivity anomaly. Arora and Subba Rao (2002) mapped South India Offshore Conductivity Anomaly (SIOCA) that correlates well with the low velocity zone and low magnetization anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Chardon et al (2011) showed that the cohesive textural fabric pattern throughout the Dharwar craton is consistent with the effects of eastward subduction on the overriding block. Finally, eastward subduction is suggested through various geophysical observations (Gupta et al, 2003b;Gokarn et al, 2004).…”
Section: Implications For the Geodynamic Evolution Of The Dharwar Cratonmentioning
confidence: 97%